2008
DOI: 10.1021/es800408u
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal Effect of Zero-Valent Iron Nanoparticles on Escherichia coli

Abstract: Zero-valent iron nanoparticles (nano-Fe0) in aqueous solution rapidly inactivated Escherichia coli (E. coli). A strong bactericidal effect of nano-Fe0 was found under deaerated conditions, with a linear correlation between log inactivation and nano-Fe0 dose (0.82 log inactivation / mg/L nano-Fe0 · hr). The inactivation of E. coli under air saturation required much higher nano-Fe0 doses due to the corrosion and surface oxidation of nano-Fe0 by dissolved oxygen. Significant physical disruption of the cell membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
375
4
6

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 685 publications
(422 citation statements)
references
References 37 publications
16
375
4
6
Order By: Relevance
“…One possible explanation is the physical disruption of cell membranes by nZVI. It can also enhance the biocide effect of Fe (Lee et al, 2008). Toxicity to microorganisms is also observed with other Fe-or Mn-containing nanoparticles (Bellusci et al, 2014).…”
Section: Effects Of Fe or Mn Compoundsmentioning
confidence: 97%
“…One possible explanation is the physical disruption of cell membranes by nZVI. It can also enhance the biocide effect of Fe (Lee et al, 2008). Toxicity to microorganisms is also observed with other Fe-or Mn-containing nanoparticles (Bellusci et al, 2014).…”
Section: Effects Of Fe or Mn Compoundsmentioning
confidence: 97%
“…As reported, the removal of bacteriophage f2 by NZVI involved the generation of intermediates, such as Fe 2þ , Fe 3þ , reactive oxygen species (Fe(IV), $OH and $O 2 À ), originated from the Fe-participated reactions (Lee et al, 2008b;Kim et al, 2011). In order to investigate which one of the intermediates played a dominant role in the bacteriophage f2 removal, a series of experiments were carried out as follows.…”
Section: The Iron Released Into the Systemmentioning
confidence: 99%
“…It indicated that Fe(III) made little contribution to the removal of bacteriophage f2. It is likely that limited solubility of Fe(III) made the removal of virus be difficult under neutral pH circumstances (Lee et al, 2008b;Keenan and Sedlak, 2008).…”
Section: Bacteriophage F2 Removal By Fe(ii)/fe(iii) Under Anaerobic/ mentioning
confidence: 99%
See 2 more Smart Citations